The Role of Croatia in Pan-European Corridors: Impact on Croatian Export - Ivan Karatović; Helena Miloloža (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
International exchange provides the implementation of significant cargo flows that connect the largest industrial, transportation and commercial world centers. By joining the European Union, Croatian transport infrastructure has become a part of the European transport network. Pan-European transport corridors are defined traffic routes in Central and Eastern Europe that contribute to cohesion of the countries through which these routes pass. Croatia, as part of Pan-European transport corridor network, is intensively involved in the plans for its development. Additionally, Croatia has finally acquired preconditions to start the implementation of an intensive linkage of the reference points of which Croatian economy, but also the whole region, will have benefits. However, without investing in the reconstruction of railways, roads and inland waterways, it is impossible to improve the international activity of Croatia. Therefore, the emphasis of this paper is in pointing out the importance of generation the single program which includes complete Croatian transport system. The great plan must be based on coherent policy and long-term strategy because only such an approach can transfigure Croatia into a serious and equal partner in the European Union.
Keywords: R40; F02; 330; Pan-European corridors; transportation; goods flow; Croatia; economy; development; Croatian export